Creation of a Tool for Assessing Knowledge in Evidence-Based Decision-Making in Practicing Health Care Providers. Issue 3 (2016) - Spurr, Kathy; Dechman, Gail; Lackie, Kelly; Gilbert, Robert
Abstract : Introduction: Evidence-based decision-making (EBDM) is the process health care providers (HCPs) use to identify and appraise potential evidence. It supports the integration of best research evidence with clinical expertise and patient values into the decision-making process for patient care. Competence in this process is essential to delivery of optimal care. There is no objective tool that assesses EBDM across HCP groups. This research aimed to develop a content valid tool to assess knowledge of the principles of evidence-based medicine and the EBDM process, for use with all HCPs. Methods: A Delphi process was used in the creation of the tool. Pilot testing established its content validity with the added benefit of evaluating HCPs' knowledge of EBDM. Descriptive statistics and multivariate mixed models were used to evaluate individual survey responses in total, as well as within each EBDM component. Results: The tool consisted of 26 multiple-choice questions. A total of 12, 884 HCPs in Nova Scotia were invited to participate in the web-based validation study, yielding 818 (6.3%) participants, 471 of whom completed all questions. The mean overall score was 68%. Knowledge in one component, integration of evidence with clinical expertise and patient preferences, was identified as needing development across all HCPs surveyed. Discussion: A content valid tool for assessing HCP EBDM knowledge was created and can be used to support the development of continuing education programs to enhance EBDM competency.